DAMPAK PENGHAPUSAN PAJAK PERTAMBAHAN NILAI PADA PEMBIAYAAN MURABAHAH TERHADAP KINERJA KEUANGAN BANK SYARIAH - Rita Yuliana; Nurul Herawati (Universitas Trunojoyo Madura, 2014)
The objective of this research is to explore the effect of Value-added Tax abolition to murabahah financing of syariah banks which refers to Tax Law No. 42 in 2009 and Finance Minister Regulation No. 251/PMK.011/2010. Using sequential data (2008:12-2012:12), this research tests financial performance: profitability and return on assets (ROA) of syariah banks, before and after the implementation of Tax Law No.42 in 2009 and the Financial Minister Regulation; and compare it to the conventional banks performance. The result suggests that there is a difference between murabahah financing before and after the implementation of the regulation. In addition, the results show that there is profitability difference between those before and after December 2010, but not for the ROA. The comparison of profitability and ROA between syariah and conventional banks shows the difference between the two. The contribution of this research is to show that the Value-added Tax abolition policy has an effect on the syariah banks performance, but not yet aligned with the conventional banks. Hence, The Central Bank effort to align syariah and conventional banks still needs to be improved.